High proton conductivity behavior in a 2D metal sulfite constructed from a histidine ligand. Issue 28 (22nd May 2019) - Ma, Yike; Huang, Liangliang; Xiu, Zhijia; Yang, Yuheng; Wang, Xiaodong; Yin, Yanzhen; Bi, Yanfeng; Zheng, Zhiping
Abstract : In the presence of the amino acid histidine, an inorganic–organic hybrid metal sulfite (compound1 ), has been prepared under hydrothermal conditions. Compound1 shows a high proton conductivity of, approximately 10 −3 S cm −1 at 348 K and 98% RH. Abstract : In the presence of the amino acid histidine, an inorganic–organic hybrid metal sulfite, Zn2 (SO3 )2 (C6 N3 O2 H9 )2 ·H2 O (1 ), has been prepared under hydrothermal conditions. Single-crystal X-ray diffraction analysis reveals that1 shows a 2D layer framework built up from a classical second building unit (S4R), and bridged histidine molecule. Notably, it is the first report of a metal sulfite in the presence of an amino acid molecule. A 1D H-bonding array can be constructed by the H-bonding interaction between histidine molecules and sulfite groups. Moreover, a new function of metal sulfite for proton conduction was investigated by alternating-current impedance analysis. The results demonstrate that compound1 shows a high proton conductivity of approximately 10 −3 S cm −1 at 348 K and 98% relative humidity.